Factors Influence Sukuk and Conventional Bonds in Malaysia - Elkarim, Ghemari Abd (2012)
The study attempts to investigate the impact influence of macroeconomic variables on Sukuk and conventional bonds issuance during periods that include the Malaysian period of economic crisis. This study examines three variables in relation to Sukuk and conventional bonds issuance for the period of 1990-2011: (i) gross domestic product (GDP), (ii) inflation rate, and (iii) interest rate. The results of the regression analysis for Sukuk indicate that, there is a negative effect and significant relationships between GDP, inflation rate and interest rate with Sukuk issuance. However, for conventional bonds, only GDP shows a significant negative effect on the relationship.